2012
DOI: 10.1111/j.1471-0528.2012.03493.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin in the prevention of pre‐eclampsia in high‐risk women: a randomised placebo‐controlled PREDO Trial and a meta‐analysis of randomised trials

Abstract: Objective To study the effect of aspirin in the prevention of pre-eclampsia in high-risk women.Design Randomised, double-blinded, placebo-controlled trial.Setting Maternity clinics in ten Finnish hospitals participating in the PREDO Project.Sample A total of 152 women with risk factors for pre-eclampsia and abnormal uterine artery Doppler velocimetry.Methods Participants were randomised to start either aspirin 100 mg/day or placebo at 12 + 0 to 13 + 6 weeks + days of gestation. Because of the limited power of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 22 publications
3
116
0
4
Order By: Relevance
“…4,5,25 The women were recruited to the study when they visited antenatal clinics at one of the 10 study hospitals in Southern and Eastern Finland for their first ultrasound screening between 12þ0 and 13þ6 weeksþdays of gestation. Of these women, 3,402 (71.2% of those with live-born offspring) filled in the biweekly depressive symptoms questionnaire during pregnancy.…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,25 The women were recruited to the study when they visited antenatal clinics at one of the 10 study hospitals in Southern and Eastern Finland for their first ultrasound screening between 12þ0 and 13þ6 weeksþdays of gestation. Of these women, 3,402 (71.2% of those with live-born offspring) filled in the biweekly depressive symptoms questionnaire during pregnancy.…”
Section: Methods Participantsmentioning
confidence: 99%
“…25 These included pre-pregnancy obesity (BMI !30 kg/m 2 vs. BMI <30 kg/m 2 ), hypertension spectrum pregnancy disorders (preeclampsia, gestational hypertension; yes/no), and gestational diabetes (yes/no). 21,25,34,35 Covariates These included maternal age at delivery (years), smoking during pregnancy (did not smoke/quit during first trimester/smoked throughout pregnancy), parity (primiparous/multiparous), chronic hypertension (yes/no), type 1 diabetes (yes/no), child's sex, gestational length (weeks), birthweight (grams), and family structure at childbirth (cohabitation/marriage vs. single parent), with data extracted from medical reports and/or Medical Birth Register; maternal history of physician-diagnosed depression before pregnancy (yes/no), psychotropic medication use during pregnancy (antidepressants, other [barbiturates, sedatives, antipsychotics] vs. no), alcohol use during pregnancy (yes/no), and education level (basic/secondary vs. tertiary), each self-reported in a questionnaire given to the mothers at 12þ0 to 13þ6 weeksþdays of gestation; and …”
Section: Pregnancy Disordersmentioning
confidence: 99%
“…146 This is thought to be the mechanism for low-dose aspirin treatment in prevention of preeclampsia in a subset of cases. 141 Of special interest was the correlation of placental metabolite pro les and maternal serum markers of preeclampsia. Glycerophosphocholine in particular correlated to increasing maternal serum sFlt-1 levels, which established a link between maternal and placental disease (paper III).…”
Section: Placental Metabolism In Active Preeclampsiamentioning
confidence: 99%
“…They keep a good balance between prostacyclin, a vasodilator, and thromboxane, a vasoconstrictor, and stimulant of platelet aggregation [20]. However, according to the studies included in this review, Aspirin does not show any significant benefits in the incidence of proteinuric pre-eclampsia, preterm delivery, birthweight or of stillbirth, placental ab- Although, a meta-analysis suggested that low-dose aspirin initiated before 16 weeks of gestation reduces the risk of pre-eclampsia (RR 0.6, 95% CI 0.4 -0.8) and severe pre-eclampsia (RR 0.3, 95% CI 0.1 -0.7) [20].…”
Section: Aspirinmentioning
confidence: 99%
“…They keep a good balance between prostacyclin, a vasodilator, and thromboxane, a vasoconstrictor, and stimulant of platelet aggregation [20]. However, according to the studies included in this review, Aspirin does not show any significant benefits in the incidence of proteinuric pre-eclampsia, preterm delivery, birthweight or of stillbirth, placental ab- Although, a meta-analysis suggested that low-dose aspirin initiated before 16 weeks of gestation reduces the risk of pre-eclampsia (RR 0.6, 95% CI 0.4 -0.8) and severe pre-eclampsia (RR 0.3, 95% CI 0.1 -0.7) [20]. Similarly, the results obtained in another review [11] shows that antiplatelet agents, mostly low-dose aspirin, have moderate benefits (up to 17% reduction in the risk of pre-eclampsia (RR 0.83, 95% CI 0.77 to 0.89) [11], when used for prevention of pre-eclampsia and its complications.…”
Section: Aspirinmentioning
confidence: 99%